Chlamydomonas reinhardtii swimming in the Plateau borders of 2D foams. Issue 1 (6th November 2020) - Tainio, Oskar; Sohrabi, Fereshteh; Janarek, Nikodem; Koivisto, Juha; Puisto, Antti; Viitanen, Leevi; Timonen, Jaakko V. I.; Alava, Mikko
Abstract : Living phototactic algae cells swim in foam films with adjusted speeds controlled by the fluidic channel width. Abstract : Unicellular Chlamydomonas reinhardtii micro-algae cells were inserted into a quasi-2D Hele-Shaw chamber filled with saponin foam. The movement of the algae along the bubble borders was then manipulated and tracked. These self-propelled particles generate flow and stresses in their surrounding matter. In addition, the algae possess the capability of exerting forces that alter bubble boundaries while maintaining an imminent phototactic movement. We find that by controlling the gas fraction of the foam we can change the interaction of the algae and bubbles. Specifically, our data expose three distinct swimming regimes for the algae with respect to the level of confinement due to the Plateau border cross-section: unlimited bulk, transition, and overdamped regimes. At the transition regime we find the speed of the algae to be modeled by a simple force balance equation emerging from the shear inside the Plateau border. Thus, we have shown that it is possible to create an algae-friendly foam while controlling the algae motion. This opens doors to multiple applications where the flow of nutrients, oxygen and recirculation of living organisms is essential.